Analisis Komparabilitas Antara PSAK 109 dengan Pedoman Akuntansi Perbankan Indonesia Buku 1 dan 2 - Diah Aryati (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
This research analyzes the Indonesian Banking Accounting Guidelines Books 1 and 2, as there have been many changes in accounting regulations within the banking industry. This change is important to discuss because it affects accounting practices in the banking industry, particularly in terms of risk management and financial statement preparation. Comparative descriptive analysis, along with a qualitative approach, was used in this study. This data was collected from banking regulations, Bank Mega Syariah's financial statements, and relevant accounting standards. The analysis method used compares old and new practices in the categorization of financial assets, measurement, and how these impact financial statements. Studies show that the implementation of PSAK 109 significantly changes credit loss provisions (CKPN); this differs from PAPI, which is more conservative in recognizing credit risk, requiring banks to calculate provisions based on long-term loss expectations. Despite some difficulties in adjusting its risk recording and measurement system, Bank Mega Syariah has begun to adopt PSAK 109. It is hoped that this research will assist academics, banking practitioners, and regulators in understanding the impact of the transition to banking accounting standards and provide a reference for further research on how it affects bank financial performance.